Paediatric Endoscopy Global Rating Scale: Development of a Quality Improvement Tool and Results of a National Pilot. Issue 2 (August 2019) - Narula, Priya; Broughton, Raphael; Howarth, Lucy; Piggott, Anna; Bremner, Ronald; Tzivinikos, Christos; Gillett, Peter; Henderson, Paul; Rawat, David; Cullen, Mick; Loganathan, Sabari; Devadason, David; et al.
ABSTRACT: Introduction and Objectives: The endoscopy Global Rating Scale (GRS) is a web-based self-assessment quality improvement (QI) tool that provides a framework for service improvement. Widespread use of the GRS in adult endoscopy services in the United Kingdom (UK) has led to a demonstrable improvement in quality. The adult GRS is not directly applicable to paediatric endoscopy services. The objective of this study is to develop and pilot a paediatric endoscopy Global Rating Scale (P-GRS) as a QI tool. Methods: Members of the British Society of Paediatric Gastroenterology, Hepatology and Nutrition (BSPGHAN) Endoscopy Working Group collaborated with the Joint Advisory Group on Gastrointestinal Endoscopy (JAG) to develop the P-GRS. After a period of consultation, this was piloted nationally at 9 centres and data were collected prospectively at 2 census points, May and December 2016. Results: The P-GRS mirrors the adult GRS by dividing care into 4 domains and includes 19 standards with several measures that underpin the standards. Eight services completed the online P-GRS return in May 2016 and 6 in December 2016. All pilot sites identified areas that needed improvement and post-pilot reflected on the key challenges and developments. Several positive developments were reported by the pilot sites. Conclusions: The national pilot helped ensure that the P-GRS developed was relevant to the paediatric endoscopy services. The pilot demonstrated that even in the first year of engaging with this QI tool, services were starting to identify areas that needed improvement, share best practice documents, put in place QI plans, and support greater patient involvement in services.